SYNTHESIS AND CHARACTERIZATION OF SUPERABSORBENT POLYMER COMPOSITES BASED ON ACRYLIC ACID, ACRYLAMIDE AND BENTONITE - A. Zainal Abidin; I. Noezar; Ridhawati Ridhawati (Jurnal Sains Materi Indonesia, 2011)
SYNTHESIS AND CHARACTERIZATION OF SUPERABSORBENT POLYMER COMPOSITES BASED ON ACRYLIC ACID, ACRYLAMIDE AND BENTONITE. Superabsorbent polymer (SAP) is a hydrogel material which is capable of absorbing and or storing liquid up to a hundred times of its dry weight. SAP was synthesized from monomers of acrylic acid and acrylamide. Beside that a superabsorbent polymer composite (SAPC) was also made by grafting the SAP with bentonite. The polymerization processes were carried out using a chemical method of a ammonium persulphate (APS) as chemical initiator and N,N-methylene bisacrylamide (MBA) as crosslink forming materials at temperature of 70 oC in the 500 mL round flask. The homogeneity of the mixture was achieved by an adjustable magnetic stirrer. The result of polymer formed was identified using a FT-IR spectroscopy and the characteristic of absorption was studied using demineral water and 0.9 % NaCl solution. The maximum absorption capacity obtained from SAP is 339 g/g in water and 65 g/g in NaCl solution, while the maximum absorption rate obtained from SPAc is 19.43 g/min in water and 7.3 g/min in NaCl solution. It is interesting to note the absorption characteristic of SAP and SAPc above, the SAP is better in capacity of absorption while the SAPC is better in the rate of absorption. This phenomenon is supported by the result of morphology identification of SEM that shows the micro porous structure of SAP is bigger in number but smaller in pore sizes, while the micro porous structure of SAPC is smaller in number but bigger pore sizes.